Pricing on Value in Engineering - Rebbitt, Tom (Henry Stewart Talks, 2010)
Pricing: the basic options, The basic principle, How to determine value, Process, Value matrix, Scope, Buying criteria, Analytical hierarchy process, Window of acceptability, Qualifying value per point, Results, Conclusions